Kemampuan Numerasi Siswa Bergaya Kognitif Reflektif dan Impulsif dalam Memecahkan Masalah SPLDV - Dewi, Nikita; Nugraheni, Esti Ambar (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Numerical ability is an important ability for students to have. This study aims to analyze students’ numeracy abilities in the matter of a two-variable linear education system (SPLDV) in terms of reflective and impulsive cognitive styles, so that the research approach used is qualitative with a descriptive type of research. This study's subjects were four students divided into two reflective students and two impulsive students. The data collection technique used is the Matching Familiar Figure Test (MFFT), a numeracy skills test, interviews, and documentation. The results showed that subjects with a reflective cognitive style were able to fulfill 4 numeric indicators (understanding problems, designing problem solutions, implementing strategies, and re-examining). given has a relatively small tendency to be wrong. Whereas subjects with an impulsive cognitive style can answer all questions but only fulfill 2 numeration indicators (understanding problems and designing problem solutions), and require a fast time to solve questions, so the answers given have a relatively large tendency to be wrong.